A Way Forward Toward Professionalizing Teacher Education: A Response to the AASCU Teacher Education Task Force Survey - Easley II, Jacob (Educational (Re)naissance, 2019)
Amid countless challenges faced by teacher education, public universities, preparing a large share of the nations' teachers, are called upon to a lead the charge of moving the field forward. The American Association of State Colleges and University's Teacher Education Task Force sought to examine current conditions among member institutions. Presidents, provosts and deans of education responded to a survey with their assessment of the current status of teacher education. The results yielded six recommendations for quality teacher education programs. The latter of which stresses professionalizing the field. Further examination of the recommendations reveals gaps between the current landscape and the recommendations. It is through these gaps that a strategic means to advance the professionalization of teacher education is put forth. Advancing the professionalization of teacher education is a collaborative effort of leadership. The process demonstrates and builds momentum from positive impact on communities and the profession itself. It is undergirded by an ethical imperative.